Thyroid metastasis from hepatocellular carcinoma: a rare case report and literature review - Guan, Shasha; Ye, Qianwen; Li, Panhua; Ding, Lijuan (Frontiers in Oncology, 2025)
BackgroundThyroid metastasis is a relatively uncommon event in clinical practice, typically occurs in more prevalent primary tumors, including renal cell carcinoma and cancers of the gastrointestinal tract, lungs, and breast. The incidence of thyroid metastasis from primary hepatocellular carcinoma (HCC) is particularly infrequent. This case report outlines the clinical challenges and diagnostic pathway associated with a thyroid mass in a patient with HCC, highlighting the rarity and intricacy of such metastatic associations.Case PresentationA 51-year-old male with a long-standing history of hepatitis B-related liver cirrhosis presented with a rapidly enlarging painful left-sided thyroid mass 28 months after a diagnosis of HCC. FDG-PET/CT imaging revealed a 6 cm hypodense tumor in the left lobe of the thyroid and further fine needle aspiration cytology and biopsy (FNAB) confirmed it as a metastasis from HCC. The patient underwent transcatheter arterial chemotherapy embolization (TACE) as a first attempt to control the progress of the thyroid lesion. However, subsequent imaging showed a continued progression of the lesions in liver, along with other metastatic sites. Although multiple interventions, such as radiofrequency ablation (RFA) procedures was administered due to the progression of liver cancer and embolization therapies for the thyroid, the patient experienced significant deterioration, presenting with respiratory failure due to malignant pleural effusion.ConclusionsThis unique case highlights the importance of promptly considering persistent or newly developed thyroid nodules as indicative of metastatic disease. The identification of thyroid metastases, especially in the context of extensive organ involvement, often correlates with a poor prognosis. Given the distinctive physiological properties of the thyroid gland, multidisciplinary management may offer clinical benefits for such patients with complex metastatic profiles. Combining locoregional therapies with immunotherapy, particularly dual immunotherapy, may offer significant prognostic advantages. Nevertheless, these hypotheses need to be verified through large-scale clinical trials.